A Spatio-Temporal Examination of Canada’s Domestic Merger Activity, 1971-1991. - Aliberti, Vincenzo; Green, Milford (Cahiers de géographie du Québec, 1999)
This study examines the relationship of Canada's urban centres (Census metropolitan areas), with respect to domestic merger activity for the years 1971, 1976, 1981, 1986 and 1991. Log-linear analysis is employed to provide a descriptive examination of the spatial merger flows for the years in question. It has been determined that from an acquiring and acquired firm perspective, Toronto, Montréal, Calgary and Vancouver, were the cities where the greatest number of merger activity was conducted.